2017
DOI: 10.1111/jocd.12377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microneedling with 70% glycolic acid peel vs microneedling alone in treatment of atrophic acne scars—A randomized controlled trial

Abstract: Addition of sequential 70% glycolic acid peel to microneedling gives better scar improvement as compared to microneedling alone. In addition to this, it also improves skin texture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Compared to another laser therapy, as a fractionated microneedle radiofrequency, a study showed that both 1550 nm Er: Glass fractional laser and fractionated microneedle were comparable based on the ECCA grading scale 25 . Moreover, MN in combination with 70% glycolic acid peel showed better improvement than MN therapy alone 26 . A prospective study also found MN and Jessner's solution dual therapy was superior compared to monotherapy 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to another laser therapy, as a fractionated microneedle radiofrequency, a study showed that both 1550 nm Er: Glass fractional laser and fractionated microneedle were comparable based on the ECCA grading scale 25 . Moreover, MN in combination with 70% glycolic acid peel showed better improvement than MN therapy alone 26 . A prospective study also found MN and Jessner's solution dual therapy was superior compared to monotherapy 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies also found that patient satisfaction was higher when MN was performed as dual therapy, such as the combination of fractionated MN radiofrequency as well as when combined with polylactic acid 28,29 . Other combination therapies with better patient satisfaction than MN therapy alone were Jessner's solution and 70% glycolic acid 26,27 …”
Section: Resultsmentioning
confidence: 99%
“…Microneedling with either derma-pen or dermaroller combined with various chemical peels and other agents like platelet rich plasma (PRP) and glycolic acid has been researched extensively to find out the right combination with best results. [11][12][13] We also used such a combination that included microneedling with dermaroller, alternating with a medium depth chemical peel 30% TCA and the results have turned out be highly significant for improvement in acne scar grading from baseline. The improvement was observed more in the acne scars having grade IV at baseline (week=0) as compared to the ones having grade III.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Significant improvement in acne scars and skin texture has been shown with a combined sequential treatment of microneedling and glycol acid peel. 14,18 Subcision (subcutaneous incisionless surgery) is a non-operative technique that involves a needle being inserted percutaneously to release fibrotic scar bands in the dermis and subcutaneous tissue, similar to a "mini-scalpel". This approach results in a tethered scar being "released" and allows neocollagenesis to take place beneath the scar, helping to lift and smooth the surface contour.…”
Section: -13mentioning
confidence: 99%